(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background:Schizophrenia is a debilitating mental illness that affects 1% of the population in all cultures. Objective: To investigate causal beliefs regarding schizophrenia among families of Iraqi schizophrenic inpatients, and discuss the differences and similarities across cultures. Methods: Two hundred Iraqi schizophrenic inpatients fulfilling DSM-IV criteria of schizophrenia were included. Causal beliefs of their key relatives were examined. Information list including open question of the causal beliefs of schizophrenia and sociodemographic data was used. The statistical significance of the findings was tested. Results: Key relatives attributed natural causes to schizophrenia more often than supernatural causes. Stress was 44%. Stresses were related to life events, trauma, social problems, war, prison and poverty. Other causes were: 27% organic and 15% personality attributions. Supernatural causal beliefs were only 29%, including witchcraft, envy, possession, devil, karama and wish or punishment of God. Conclusions: The major causal beliefs of schizophrenia amongst Iraqi relatives of the studied sample were stresses. Families’ attribution of supernatural causes was similar across cultures. Organicity was more in the European studies. Key Words: Schizophrenia, causes, beliefs, families, Iraq.